Fiber-enriched calcium phosphate cement implanted in the femur of rats: a histological evaluation. (Revista da Faculdade de Odontologia - UPF, 2014)
We performed a histological analysis of nylon, carbon, and polypropylene fiber-enriched calcium phosphate cement (CPC) for use as bone substitute in the femur or rats. Fiber-enriched CPC blocks (6-mm diameter, 2-mm thickness) were implanted in the femur of 20 male Wistar rats. The animals were euthanized at 30, 60, 90, and 120 days, with removal and histological evaluation of the specimens. Biocompatibility, resorption and osteoconduction were evaluated. At all time points, histological analysis revealed the formation of dense connective tissue with low cellularity, little vascularization and a few mononuclear cells. Surrounding the implant, slight resorption and hyalinization of peripheral collagen fibers were observed, with evidence of incorporation of implant material into connective tissue. Osteoid tissue was observed at 120 days. Bone resorption surrounding the implant was not significant. Based on the present criteria, CPC seems adequate for use as a bone substitute.Keywords: Biomaterials. Bone substitutes. Calcium Phosphate Cements.